The Effect of Health Center Facilities on Patient Satisfaction in Ambulantory Installations - mochammad Malik Ibrahim; Sagita Candra Puspitasari (EDUPEDIA Publisher, 2023)
Objective: This study aims to analyze the effect of facilities on patient satisfaction at the Pandaan Health Center. Methods: This type of research is a quantitative analytic cross-sectional design. The population numbered around 1,568 patients with a total sample of 94 patients in ambulantory installations. Sampling technique with accidental sampling. The instrument measurement scale uses a Likert scale. Primary data collection methods using questionnaires and data analysis kolmogorov smirnov data normality test, linearity test, spearman correlation and logistic regression enter method. Results: The results showed that the variable of facilities proved to have an effect on patient satisfaction with a significant value (p=0.016, POR=3). Conclusion: The health center facilities are one of the factors that influence patient satisfaction at the Pandaan Health Center.